2017
DOI: 10.1007/11157_2017_12
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Geochemistry and Volcanic Unrest: Dissolving the Haze in Time and Space

Abstract: The heat and gas released by a degassing magma affects the overlying predominantly meteoric aquifers to form magmatic-hydrothermal systems inside the solid body of a volcano. This chapter reviews how fluid geochemical signals help to track the evolution throughout the various stages of volcanic unrest. A direct view into a degassing magma is possible at open-conduit degassing volcanoes. Nevertheless, in most cases gas is trapped (i.e. scrubbed) by abundant water, leading to the loss of the pure signal the magm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In this regard, detection of a magmatic chamber containing some melt fraction could mean the potential for reactivation even after several tens of kiloyears dormancy. Emission of gases with isotopic signatures in the range of magmatic values can be evidence of magma intrusions at depth (Bräuer et al, 2008(Bräuer et al, , 2018Caracausi et al, 2013Caracausi et al, , 2015Carapezza et al, 2003Carapezza et al, , 2012Carapezza & Tarchini, 2007;Farrar et al, 1995;Pizzino et al, 2002;Rouwet et al, 2014Rouwet et al, , 2017Sano et al, 2015;Sorey et al, 1998), in addition to recognition of geophysical anomalies reflecting melt pockets at depth (Comeau et al, 2015(Comeau et al, , 2016Harangi, Novák, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, detection of a magmatic chamber containing some melt fraction could mean the potential for reactivation even after several tens of kiloyears dormancy. Emission of gases with isotopic signatures in the range of magmatic values can be evidence of magma intrusions at depth (Bräuer et al, 2008(Bräuer et al, , 2018Caracausi et al, 2013Caracausi et al, , 2015Carapezza et al, 2003Carapezza et al, , 2012Carapezza & Tarchini, 2007;Farrar et al, 1995;Pizzino et al, 2002;Rouwet et al, 2014Rouwet et al, , 2017Sano et al, 2015;Sorey et al, 1998), in addition to recognition of geophysical anomalies reflecting melt pockets at depth (Comeau et al, 2015(Comeau et al, , 2016Harangi, Novák, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some research has examined this question from an opposite standpoint and focusses instead on how volcanic activity increases seismicity 5,6 .Alterations in volcanic activity are observed after an increase in seismicity at both short (< 100 km) and long (> 500 km) distances from the epicenter [7][8][9][10] . Other manifestations related to seismic events observed in volcanoes include variations in deformation rates 7,11,12 , degassing and heat flux [13][14][15] , and phreatic activity [16][17][18][19] .…”
mentioning
confidence: 99%
“…It has been observed that modest, proximal earthquakes can cause an increase in near-vent permeability and trigger mild bursts of hydrothermal fluids (Hurwitz et al 2014;Reed et al 2021). Large events may cause rock fracturing to break aquifer seals or produce seismic waves that can perturb hydrothermal systems over different timescales and distances (Rouwet et al 2019;González et al 2021). For instance, the M7.6 Nicoya earthquake in Costa Rica in 2012 enhanced seismic and thermal activity at Irazú-Turrialba and Poás volcanoes ) and affected the eruptive activity in the following 2 to 5 years (de Moor et al 2017;Salvage et al 2018).…”
Section: Triggersmentioning
confidence: 99%